Profezia e politica all'alba dei tempi moderni - Barbuto, Gennaro Maria; Seller, Fabio (Clio. Essays in History, Archaeology and Art History, 2024)
The volume, which collects the proceedings of a seminar held in October 2022 at the DSU of the University of Naples Federico II, aims to offer a contribution on an essential theme of historical-intellectual research at the origins of modern age, namely the relationships between prophecy and politics. From the essay on the figure of the prophet in the thought of Max Weber, which takes on the role of a methodological overture, and from Savonarola to Machiavelli, Guicciardini, Bodin, the Libertines, Campanella, what is diplayed is a series of contributions on authors who, in a deep and peculiar way, faced the relationships between prophecy and politics in an era of great upheavals and innovations.